Development and external validation of the 'Flower-FFQ': a FFQ designed for the Lifelines Cohort Study. Issue 2 (14th February 2022) - Brouwer-Brolsma, Elske M; Perenboom, Corine; Sluik, Diewertje; van de Wiel, Anne; Geelen, Anouk; Feskens, Edith JM; de Vries, Jeanne HM
Abstract: Objective: FFQ assess habitual dietary intake and are relatively inexpensive to process, but may take up to 60 min to complete. This article describes the validation of the Flower-FFQ, which consists of four short FFQ measuring the intake of energy and macronutrients or specific (micro)nutrients/foods that can be merged into one complete daily assessment using predefined algorithms. Design: Participants completed the Flower-FFQ and validated regular-FFQ ( n 401). Urinary N ( n 242) and K excretions ( n 361) were measured. We evaluated: (1) group-level bias, (2) correlations and (3) cross-classification. Setting: Observational study. Participants: Dutch adults, 54 ± 11 (mean ± SD) years. Results: Flower-FFQ1, Flower-FFQ2, Flower-FFQ3 and Flower-FFQ4 were completed in ±24, 9, 8 and 9 min (±50 min total), respectively. The regular-FFQ was completed in ±43 min. Mean energy (flower v . regular: 7953 v . 8718 kJ/d) and macronutrient intakes (carbohydrates: 204 v . 222 g/d; protein: 75 v . 76 g/d; fat: 74 v . 83 g/d; ethanol: 8 v . 12 g/d) were comparatively similar. Spearman correlations between Flower-FFQ and regular-FFQ ranged from 0·60 to 0·80 for macronutrients and from 0·40 to 0·80 for micronutrients and foods. For all micronutrients and foods, ≥ 78 % of the participants classified in the same/adjacent quartile. The Flower-FFQ underestimated urinary N and K excretions by 24 and 18 %; 75 and 73 % of the participants ranked in the same/adjacent quartile. Conclusion: Completing the Flower-FFQ required 50 min with a maximum of 25 min per short FFQ. The Flower-FFQ has a moderate to good ranking ability for most nutrients and foods and performs sufficiently to study diet–disease associations.